Music and the origins of language : theories from the French Enlightenment - Thomas, Downing A. (New perspectives in music history and criticism., 1995)
The search for the origins of language was one of the most pressing philosophical issues of the eighteenth century. What has often escaped notice, however, is the fact that music figures prominently in this search. This study analyses instances of thinking or reasoning about music and music theory as they appear within the logical and narrative structure of contemporary texts, including writings by Rousseau, Diderot, Rameau and Condillac. These can only be properly understood as part of an interdisciplinary project, as situated within a field of larger cultural issues and concerns. The author is interested in the ways in which music functions within this discursive framework to facilitate links between language and meaning, and between conceptions of an original society and an ideal social order.